Evaluation of elite table tennis players` comprehensive technical and tactical performance - Chen, Z.; Li, M.; Yang, Q. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Game performance analysis has been playing a significant role in sports events which has reached an international consensus. In the field of technical and tactical analysis of table tennis, many studies conducted the segmented evaluation of players based on the phased-theory. The present study proposed the concepts of "competitive technical and tactical performance" of elite table tennis players. The purpose of this study was to develop an entropy-based weighting system integrated with three comprehensive evaluation methods, aiming to examine its feasibility for evaluation in two practical applications: inter-athlete comparison and performance fluctuations across time periods. Another purpose was to explore the applicability of different comprehensive evaluation methods through comparative application.